Ab initio tertiary-fold prediction of helical and non-helical protein chains using a genetic algorithm - Dandekar, Thomas; Argos, Patrick (International journal of biological macromolecules, 1996)
In this study, protein structures were predicted using a genetic algorithm. Optimal structures were selected according to basic protein-building principles. Having previously applied this approach to proteins with helical topology, this paper reports preliminary results on 3 proteins with mixed topology (helical and non-helical, e.g. sheet). The method seems to be generally applicable to protein-fold prediction since topology predictions close to the observed experimental structures are obtained.